Suppressor of cytokine signalling 1 in lymphocytes regulates the development of intestinal inflammation in mice. Issue 2 (24th August 2005) - Inagaki-Ohara, K; Sasaki, A; Matsuzaki, G; Ikeda, T; Hotokezaka, M; Chijiiwa, K; Kubo, M; Yoshida, H; Nawa, Y; Yoshimura, A
Abstract : Background and aims: Imbalance between pro- and anti-inflammatory cytokines produced by intestinal T cells induces inflammatory bowel diseases (IBD). However, the importance of regulation of cytokine signalling in IBD has not been fully clarified. We have demonstrated that suppressor of cytokine signalling 1 (SOCS1) is expressed in inflamed tissues in an experimental colitis model. In the present study, we investigated the role of SOCS1 in colitis models to clarify the mechanism of IBD development. Methods: Intestinal T cells in transgenic mice expressing high levels of SOCS1 in lymphocytes (SOCS1Tg mice) were characterised by flow cytometric analysis and cytokine production from intestinal T cells was determined by ELISA. 2, 4, 6-Trinitrobenzene sulphonic acid (TNBS) induced colitis was induced in SOCS1Tg mice and severity was compared with control littermates by measurement of survival rates. Intracellular signalling was assessed by western blotting analysis. Results: SOCS1Tg mice developed colitis spontaneously with age. Young SOCS1Tg mice less than 15 weeks of age, before the onset of colitis, were susceptible to TNBS induced colitis. Intestinal T cells of SOCS1Tg mice showed increased interferon γ and tumour necrosis factor α production and decreased transforming growth factor β production. Expression of cytotoxic T lymphocyte associated antigen 4 (CTLA-4), a negative regulator of T cell activation, in SOCS1Tg mice was severely impaired at the protein level although mRNA levels of CTLA-4 in SOCS1Tg mice were comparable with those in control mice. Conclusions: Our data suggest that SOCS1 plays an important role in the regulation of colitis by controlling intestinal T cell activation mediated through CTLA-4 expression.